Position Periodic Control of Two Rotating Airplanes - José Antonio Bautista-Medina; Rogelio Lozano; Antonio Osorio-Cordero (Drones, 2022)
The increasing development in aerial vehicles shows a wide range of configurations for different requirements. Many of them combine conventional configurations’ features to take advantage of their qualities, such as performing a cruise flight as an airplane and hovering like a helicopter. Thereby, this study analyzes the modeling and control of a pair of fixed-wing airplanes joined together to form a larger rotor that incorporates valuable features in missions with aerial vehicles. The model uses the Lagrange approach to obtain the motion equations in the flight plane, and two control strategies are proposed to regulate the movement in the horizontal plane: a cyclic proportional derivative control and a positive function. Both controls generate a sinusoidal signal to regulate the thrust of the motors, and this leads to the generation of pulses that direct and move the vehicle toward a desired position until it is reached. Our analysis is validated by simulation that shows how both controls govern the center of mass position of the rotating planes, and it also shows the airplanes’ trajectory. The results show good performance.